Nutritional Supplementation of Naturally Occurring Vitamin D to Improve Hemorrhagic Stroke Outcomes - Ashouri, Rani; Fangman, Madison; Brielmaier, Jordan; Fields, Zoe A.; Campo, Natalie; Doré, Sylvain (Frontiers in Neurology, 2021)
Vitamin D deficiency, if left untreated, is associated with bone disorders, cardiovascular damage, and an increased risk of ischemic stroke. While there are various nutritional options for the natural intake of vitamin D, we hope to elucidate the potential mechanisms dietary vitamin D may play in hemorrhagic stroke pathology. This scoping review outlines findings from studies relevant to the biochemical activity of vitamin D, the impact of vitamin D deficiency on hemorrhagic stroke outcomes, and the potential benefit of nutritional vitamin D on hemorrhagic stroke outcomes. Here, we analyze the relevant factors that can lead to vitamin D deficiency, and subsequently, a higher risk of hemorrhagic stroke incidence with worsened subsequent outcomes. The neuroprotective mechanisms through which vitamin D works to attenuate hemorrhagic stroke onset and post-stroke outcomes have not yet been thoroughly examined. However, researchers have proposed several potential protective mechanisms, including reduction of blood brain barrier disturbance by inhibiting the production of reactive oxygen species, mitigation of inflammation through a reduction of levels of proinflammatory cytokines, and prevention of cerebral vasospasm and delayed cerebral ischemia following subarachnoid hemorrhage and intracerebral hemorrhage. While more research is needed and there are limitations to vitamin D supplementation, vitamin D as a whole may play a significant role in the dynamics of hemorrhagic stroke. Further research should focus on expanding our understanding of the neuroprotective capacity and mechanisms of vitamin D, as well as how vitamin D supplementation could serve as an effective course of treatment of hemorrhagic strokes.